EVALUATING USERS’ SATISFACTION ON ACADEMIC LIBRARY PERFORMANCE - Ahmad Kassim, Norliya (Malaysian Journal of Library and Information Science, 2009)
This paper reports a part of a quantitative study that aims to evaluate the library’s performance by measuring the users’ satisfaction with (a) library services, (b) infrastructure/place/space and (c) collection/information provided by an academic library in Malaysia. A self-developed questionnaire was used to gauge the respondents’ opinions on their satisfaction level on the statements regarding the three dimensions. The instrument was distributed to a sample of 650 final year students from three faculties of the university. Descriptive and inferential statistics were used in the analysis of data using the Statistical Product and Service Solutions. A parametric test using the one-way analysis of variance (ANOVA) was used to compare the mean satisfaction scores among the respondents from the three faculties. The results of the study revealed that on the average, the respondents were only quite satisfied with the library services, infrastructure/place/space, collection/information of the library as a whole. The respondents were relatively most satisfied with infrastructure/place/space (M= 3.41), followed by collection/information (M= 3.27), and library services to users (M= 3.18) in that order. The results also showed significant differences on the satisfaction on services, infrastructure/place/space, and libraries’ collection/information among the respondents of the three faculties.